Application of Al/B/Fe2O3 Nano Thermite in Composite Solid Propellant - Jingke Deng; Guoping Li; Lianhua Shen; Yunjun Luo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Hydroxyl-terminated polybutadiene (HTPB) propellant were prepared with different content of Al/B/Fe2O3 nano thermite, and the mechanical, thermal and energetic performances were studied. Al/B/Fe2O3 nano thermite exhibited good compatibility with HTPB and dioctyl sebacate (DOS) through differential scanning calorimetry (DSC) tests. Mechanical experiments show that the mechanical properties of HTPB propellant could be improved by the addition of a small quantity of Al/B/Fe2O3 nano thermite, compared with the absence of Al/B/Fe2O3 nano thermite. For example, with the addition of 3% Al/B/Fe2O3 nano thermite, the tensile strength and elongation of propellant had the increase of 15.3% and 32.1%, respectively. Thermal analysis indicated that the decomposition of ammonium perchlorate (AP) in HTPB propellant could be catalyzed by Al/B/Fe2O3 nano thermite, the high-temperature exothermic peak of AP was shifted to lower temperature by 70.8 °C when the content of Al/B/Fe2O3 nano thermite was 5%, and the heat released was enhanced by 70%. At the same time, the heat of explosion of HTPB propellant could also be enhanced by the addition of Al/B/Fe2O3 nano thermite.